PARTISIPASI MASYARAKAT DALAM PENANGGULANGAN SAMPAH DAN KEBERSIHAN LINGKUNGAN DI KECAMATAN SAMARINDA ULU KOTA SAMARINDA - A. Diba Dina Fachrini (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The aim of this article is to describe about the degree of participation of society in handling rubbish prolem and environment cleanness in Samarinda. The rubbish problem always becomes the actual issue in its relations to the development activity, in particular for urban areas. The study finds out that participation of society in handling the rubbish was good and right level.